Multi-Criteria Decision-Making Pemilihan Kostan Menggunakan Multi-Atributive Ideal-Real Comparative Analysis (MAIRCA) - Dwi Handoko (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2024)
The determination of boarding house is a decision that requires careful consideration to meet the needs and preferences of residents. Multi-Criteria Decision-Making (MCDM) is a systematic approach used in various fields to analyze and evaluate complex decision problems involving many conflicting criteria. The application of the MAIRCA method in determining boarding places becomes an alternative for users in choosing a location with the help of a decision support system, so that it becomes an alternative consideration in choosing and determining decisions. Alternative ranking by recommending Kost Nur with a final score of 0.110417 gets 1st place, Casablangka with a final value of 0.077500 gets 2nd place, and Rumahku with a final value of 0.076250 gets 3rd place.